The aspects of restructuring enterprises and the ways of implementing the process - Garškaitė-Milvydienė, Kristina (Business: Theory and Practice, 2014)
The paper discusses certain aspects of restructuring enterprises and presents different ways and measures applicable for restructuring companies; they are divided and grouped according to certain qualities. In scientific literature, measures for restructuring enterprises are most frequently classified according to organizational, legal, financial and strategic aspects. For assessing the factor of the period, passive and active ways for transforming enterprises are often singled out, where the first one is usually applied when the response to ongoing negative changes is late and actions are limited by operative anticrisis measures targeted for cutting expenses. When the active way to the transformation of enterprises is employed, the aim of assessing the total situation of the enterprise and newly forming its strategic potential is pursued. The measures for restructuring enterprises classified with reference to different aspects differ in their goals, contents and technologies of implementation. Variety in applicable measures is predetermined by a broad range of causes and goals, and the scope of restructuring enterprises depends on the abundance of sectors to be transformed to the enterprise. Choosing a way to restructuring enterprises is also affected by external and internal environmental factors. In practice, a combination of various ways for restructuring rather than a single one of those) is applied. Įmonių restruktūrizavimo aspektai ir jo įgyvendinimo būdai Santrauka Straipsnyje nagrinėjami tam tikri įmonių restruktūrizavimo aspektai. Pateikiamieji įvairūs įmonių restruktūrizavimo būdai ir priemonės skirstomi ir grupuojami pagal tam tikrus požymius. Mokslinėje literatūroje įmonių restruktūrizavimo būdai ir priemonės dažniausiai klasifikuojami pagal organizacinius, teisinius, finansinius ir strateginius aspektus. Įvertinant laikotarpio veiksnį, dažnai išskiriami pasyvusis ir aktyvusis įmonių pertvarkos būdai, kurių pirmasis dažniausiai taikomas, kai pavėluotai reaguojama į vykstančius negatyvius pokyčius ir apsiribojama operatyvinėmis antikrizinėmis priemonėmis, padedančiomis mažinti išlaidas. Taikant aktyvųjį įmonių pertvarkos būdą, siekiama įvertinti įmonės situaciją ir naujai suformuoti strateginį jos potencialą. Įvairiais aspektais skirstomos įmonių restruktūrizavimo priemonės skiriasi savo tikslais, turiniu ir įgyvendinimo technologija. Taikomų antikrizinių priemonių įvairovę lemia daugybė priežasčių ir tikslų, o restruktūrizavimo mastas priklauso nuo sričių gausos, reikalaujančių pertvarkų įmonėje. Įmonių restruktūrizavimo būdų pasirinkimui įtakos turi ir išoriniai bei vidiniai aplinkos veiksniai. Praktikoje įmonių restruktūrizavimo procese dažnai taikomas ne vienas kuris restruktūrizavimo būdas, o jų derinys.